E.09 Predictors of optimal endovascular therapy results among patients with acute ischemic stroke. (17th June 2016) - Catana, D; Badhiwala, J; Koziarz, A; Reddy, K; Almenawer, SA
Abstract : Background: Several studies have demonstrated the safety and efficacy of endovascular therapy for patients with acute ischemic stroke. However, patient, imaging and treatment factors associated with the optimal functional outcome require better definition.Methods: We pooled data from 8 randomized controlled trials (SYNTHESIS, MR RESCUE, IMS III, MR CLEAN, ESCAPE, EXTEND-IA, SWIFT-PRIME, and REVASCAT). We conducted subgroup and sensitivity analyses to evaluate predictors of optimal functional results (modified Rankin scale, mRS) at 90 days.Results: Meta-analysis of 8 trials including 2, 423 patients yielded that endovascular therapy resulted in 44.6% functional independence (mRS 0-2) versus 31.8% in the usual care group (OR 1.71, 95% CI 1.18-2.49, P=0.005). This treatment effect was significantly greater among patients with confirmed angiographic imaging of proximal arterial occlusion (OR 2.24, 95% CI 1.72-2.90, P<0.001), in patients who received the combined therapy of intravenous tPA and endovascular intervention (OR 2.07, 95% CI 1.46-2.92, P<0.001), and when using stent retriever for mechanical thrombectomy (OR 2.39, 95% CI 1.88-3.04, P<0.001).Conclusions: The relative functional benefit associated with endovascular therapy among patients with acute ischemic stroke was increased when combined with intravenous tPA, with confirmed proximal arterial occlusion on angiographic imaging, and with use of stent retrievers for mechanical thrombectomy.